Desert dust hazards: A global review - Middleton, N (Elsevier, 2016)
Dust storms originate in many of the world’s drylands and frequently present hazards to human society, both within the drylands themselves but also outside drylands due to long-range transport of aeolian sediments. Major sources of desert dust include the Sahara, the Middle East, central and eastern Asia, and parts of Australia, but dust-raising occurs all across the global drylands and, on occasion, beyond. Dust storms occur throughout the year and they vary in frequency and intensity over a number of timescales. Long-range transport of desert dust typically takes place along seasonal transport paths. Desert dust hazards are here reviewed according to the three phases of the wind erosion system: where dust is entrained, during the transport phase, and on deposition. This paper presents a synthesis of these hazards. It draws on empirical examples in physical geography, medical geology and geomorphology to discuss case studies from all over the world and in various fields. These include accelerated soil erosion in agricultural zones – where dust storms represent a severe form of accelerated soil erosion – the health effects of air pollution caused by desert aerosols via their physical, chemical and biological properties, transport accidents caused by poor visibility during desert dust events, and impacts on electricity generation and distribution. Given the importance of desert dust as a hazard to human societies, it is surprising to note that there have been relatively few attempts to assess their impact in economic terms. Existing studies in this regard are also reviewed, but the wide range of impacts discussed in this paper indicates that desert dust storms deserve more attention in this respect.